ANALISIS HUKUM TERHADAP KEBIJAKAN PEMERINTAH DALAM PENGEMBANGAN FINTECH DI INDONESIA - Imam Fathwa; Pandri Zulfikar; Bayu Triwibowo; Tri Susanto; Ratu Chumairoh Noor (CV. Lafadz Jaya, 2026)
The development of financial technology (fintech) in Indonesia has fundamentally transformed the paradigm of financial services, driving financial inclusion and digital economic growth. The Indonesian government, through the Financial Services Authority (OJK) and Bank Indonesia (BI), has formulated various policies to regulate and develop the fintech ecosystem. However, these policies face complex legal challenges, including the balance between innovation and financial system stability, consumer protection, and alignment with national interests. This study aims to analyze the legal framework of government policies in fintech development in Indonesia, identify regulatory gaps, and formulate improvement recommendations. The method used is normative legal research with statutory, conceptual, and comparative approaches. The results indicate that Law Number 4 of 2023 on the Development and Strengthening of the Financial Sector (P2SK Law) provides the main legal umbrella, but its implementation still faces challenges related to fragmented authority, regulatory imbalance between innovation and protection, and limited oversight of new business models such as decentralized finance (DeFi). This study recommends harmonization of regulations across agencies, strengthening of the regulatory sandbox, and establishment of a single fintech supervisory authority to enhance policy effectiveness